2014
DOI: 10.1111/dme.12553
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diabetes acceptance can help identify patients with ineffective diabetes self‐care and poor diabetes control

Abstract: Low diabetes acceptance is associated with impaired self-care and glycaemic control. Assessment of diabetes acceptance may facilitate the detection of patients at high risk and may present an essential target for treatments to improve diabetes control that is more relevant than elevated depressive mood or diabetes distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 22 publications
(25 reference statements)
6
71
0
7
Order By: Relevance
“…Furthermore, we found this association only in men with type 2 diabetes, and not in women. Clinically, dealing with diabetes distress is important because it can present a psychological obstacle to effective selfmanagement behaviours and therefore to achieving good glycaemic control [18,19]. Several studies have evaluated the association between diabetes distress and glycaemic control or diabetes complications in individuals with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found this association only in men with type 2 diabetes, and not in women. Clinically, dealing with diabetes distress is important because it can present a psychological obstacle to effective selfmanagement behaviours and therefore to achieving good glycaemic control [18,19]. Several studies have evaluated the association between diabetes distress and glycaemic control or diabetes complications in individuals with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The sixitem German version of the AADQ measures acceptance of diabetesrelated thoughts and feelings and the degree to which they interfere with valued action (10). A higher score indicates greater acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diabetes and comorbid depression report a poorer quality of life (4), reduced well-being (5), higher levels of diabetes-related distress (6,7), lower satisfaction with diabetes treatment (8), reduced diabetes self-care (9), and higher nonacceptance of diabetes treatment measures (10). In the long term, depression in diabetes is associated with a poorer prognosis with regard to microvascular or macrovascular diabetes complications (11), disability (12), and early mortality (13,14).…”
mentioning
confidence: 99%
“…However, a large part of the variance in such scales is not explained by depressive symptoms [18]. For example, a longitudinal study of 1567 individuals with diabetes found that 55% of those with diabetes distress did not have likely depression [19], while a factor analysis study reported that depression and distress symptoms could be segregated into two independent factors [20]. Clinically, diabetes distress is significant because it may be a greater psychological barrier to self-management, and therefore to optimising glycaemic control, than depressive symptoms [21,22] and it is potentially modifiable using psychological therapy [23].…”
Section: Introductionmentioning
confidence: 99%